Magnetically Recoverable Fe3O4 Nanoparticles for the One‐Pot Synthesis of Coumarin‐3‐carboxamide Derivatives in Aqueous Ethanol. Issue 26 (9th July 2018) - Payra, Soumen; Saha, Arijit; Banerjee, Subhash
Abstract: Here, we have demonstrated an efficient protocol for the synthesis of coumarin‐3‐carboxamides via one‐pot multicomponent reactions of 2‐hydroxy‐benzaldehyde, ethyl cyanoacetate and aromatic/aliphatic amines using magnetically separable nano‐Fe3 O4 as reusable catalyst in aqueous ethanol. This is the first one‐pot protocol to produce coumarin‐3‐carboxamides. The reactions are very fast (5 min.) and high yielding (74‐99%). The nano‐Fe3 O4 catalyst was separated simply by using an external magnet, after completion of the reaction and recycled up to 10 times without loss of catalytic activity. Abstract : An efficient protocol for the synthesis of coumarin‐3‐carboxamides has been demonstrated using magnetically separable Fe3 O4 nanoparticles as reusable catalyst via one‐pot multicomponent reactions in aqueous ethanol. The nano‐Fe3 O4 catalyst was recycled up to 10 times with a minimum loss of catalytic activity.